2020
DOI: 10.3390/cancers12103060
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effects of Trabectedin and Lurbinectedin on Human Macrophage Function and Fate—Novel Insights

Abstract: Background: Tumor-associated macrophages (TAMs) play a crucial role in suppressing the immunosurveillance function of the immune system that prevents tumor growth. Indeed, macrophages can also be targeted by different chemotherapeutic agents improving the action over immune checkpoints to fight cancer. Here we describe the effect of trabectedin and lurbinectedin on human macrophage cell viability and function. Methods: Blood monocytes from healthy donors were differentiated into macrophages and exposed to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…To do this, we polarized hMF and, after incubation with GCVD or GNP, we evaluated the respiratory behavior in an Agilent Seahorse XF platform. [ 45,46 ] We measured the oxygen consumption rate (OCR) in resting (hM0), proinflammatory (hM1) and anti‐inflammatory (hM2) hMF, respectively. As Figure 3 shows, GNP significantly decreased the basal OCR in hM0 and hM1, but increased this parameter in hM2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To do this, we polarized hMF and, after incubation with GCVD or GNP, we evaluated the respiratory behavior in an Agilent Seahorse XF platform. [ 45,46 ] We measured the oxygen consumption rate (OCR) in resting (hM0), proinflammatory (hM1) and anti‐inflammatory (hM2) hMF, respectively. As Figure 3 shows, GNP significantly decreased the basal OCR in hM0 and hM1, but increased this parameter in hM2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…An important specific issue of macrophage metabolism is the polarization‐dependent consumption of oxygen. [ 45,46 ] In the presence of GNP, mitochondrial oxygen consumption (the “basal” respiration value) was significantly reduced in hM0 and hM1 incubated with GNP, but increased in hM2. These data suggest that the response to the presence of GNP implies a specific action on the mitochondrial OCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this, the complexity of trabectedin mechanism of action and its potential effects on liver remain to be elucidated. Recent findings showed that it may modulate the tumor microenvironment by activating the production and the release of cytokines [51,52]. It is known that deregulation of pro-inflammatory factor production may result in the downregulation of CYP450s and other enzymes involved in drug metabolism [53].…”
Section: Discussionmentioning
confidence: 99%